THE MEASUREMENT OF INTER-PARTICLE DIFFUSION COEFFICIENTS IN MINE WASTES - Van Eck, Peter (University of Waterloo, 2021)
Acid mine drainage (AMD) is the release of acidic waters from mines, waste-rock piles and mine tailings impoundments containing high concentrations of SO4, Fe(II) and other metal(oid)s. The bulk of AMD generation occurs in the vadose zone where water and O2(g) can react with the gangue sulfide minerals present in mine waste. The ability to quantify and model the limiting reactants of water and O2(g) is vital to understanding and controlling the generation of AMD at a mine site. Characterizing the unsaturated properties of mine wastes is important for determining the rate of sulfide oxidation and the extent of AMD. Soil-water characteristic curves (SWCC) are a tool used to describe the unsaturated conditions present in mine waste. Soil-water characteristic curves were measured using matrix-matrix material (<4.75 mm) from three mine sites: Faro Mine Complex, YT; the Detour Lake Gold Mine, ON; and Diavik Diamond Mine, NT, to examine the differences in matrix-material particle-size distribution among mine sites and the effect of particle-size distribution on SWCC morphology. Estimations of effective diffusion coefficients and sulfide oxidation rates were calculated using parameters derived from these measurements. The results indicate that mine waste-rock matrix material can exhibit a high degree of hysteresis, that can result in differences between oxygen diffusion coefficients and sulfide oxidation rates during wetting and drying stages. The results contribute to the characterization of the unsaturated properties of mine wastes and provide estimates of the variation in inter-particle diffusion coefficients of mine waste in response to changing moisture content reflecting hysteresis. Laboratory column experiments were conducted to measure O2(g) diffusion rates through variably saturated waste-rock matrix material. Effective diffusion coefficients were calculated using the numerical model MIN3P for both wetting and drying phases of waste-rock matrix material to assess the impact of hysteresis on O2(g) diffusion. The calculated effective diffusion coefficients were used to estimate sulfide oxidation rates to observe potential variability in oxidation rate caused by hysteresis. The results from the SWCC measurements indicate the potential for waste-rock matrix material to exhibit a high degree of hysteresis. The results from the laboratory column experiments indicate that the effect of hysteresis on effective diffusion coefficients and sulfide oxidation rates was negligible for high values of negative matric suction. Potential concern for the impact of hysteresis on sulfide oxidation rates occurs at near zero-values of matric suction where estimated effective diffusion coefficients and sulfide-oxidation rates vary by orders of magnitude.